The Influence of Pro Evolution Soccer Game-Based Learning on Understanding Football Rules among Tenth Grade Students - Abdillah, Irvan; Siregar, Samsuddin; Burgueño , Rafael; Lea, Felisa Romo; Barton , Gertude (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. This research endeavors to examine the influence of Pro Evolution Soccer on the understanding of Soccer regulations among tenth-grade students at SMA Dharma Pancasila Medan. Materials and methods. The employed research methodology is experimental, utilizing a pretest-posttest framework devoid of a control group. The participant cohort includes 36 students, consisting of 17 males and 19 females. Data collection involved assessments of Soccer rule comprehension pre- and post-intervention, facilitated by the Pro Evolution Soccer game. Results. Data analysis indicated a substantial effect on comprehension of Soccer rules following the educational intervention utilizing the Pro Evolution Soccer game. This is supported by paired t-test findings, demonstrating that the posttest mean score (74.792) notably exceeds the pretest mean score (60.347), yielding an average difference of 14.44 and a significance level (p < 0.05). Conclusions. The study concludes that Pro Evolution Soccer effectively enhances students' comprehension of Soccer rules. Incorporating video clips into the learning approach further enriches students' understanding. The research advocates for the broader implementation of such innovative educational methods in physical education and sports to enhance learning quality and student motivation.